Numerical analysis of uplift capacity of strip plate anchors in reinforced and unreinforced cohesionless soils - Korkmaz, Bilal; Keskin, Mehmet Salih (Korean Geosynthetics Society, 2018)
In this study, the effect of the reinforced soil condition on uplift capacity of strip anchor plates is investigated with three dimensional numerical analyses. The analyses were performed both on dense and loose sand using different sizes strip anchors plates (B=L=0.5m-0.75m-1.00m) for different embedment ratios, (Df/B=1-3-5). The geogrid element was modeled as a reinforcement in the analyses and the “Hardening Soil Model” was used as a soil model. The parameters investigated are the first reinforcement layer position, number of reinforcement layers, and length of the reinforcement layers. The results proved that the reinforcement had a considerable effect on the uplift capacity of the strip anchor plates in sand. Also, the improvement in bearing capacity of strip anchor plates in sand was found to be strongly dependent on the embedment ratio, and relative density of sand. The failure mechanism of strip plate anchors which are subjected to uplift forces was investigated in both reinforced and unreiforced soil conditions in order to observe the effect of reinforcement on failure mechanism. Based on the three dimensional finite element analyses, optimum values of the geogrid parameters for maximum reinforcing effect are discussed and suggested. Copyright © 11th Inter. Conf. on Geos. 2018, ICG 2018. All rights reserved.
Keywords: Finite element method; Geogrid; Plate anchors; Sand; Uplift capacity